Scientific popularization activities for non-formal education - Correia, Marisa (2022)
Several social de ates related to environmental and health issues, such as the COV -19 pandemic and climate change, have raised ma*or concerns a out misinformation and science denialism. herefore, there is a need for pu lic understanding of ho8 science 8or+s [1] and to promote scientific literac: in the general population [2]. opularization of science ac2uires a uni2ue importance in the construction of a democratic societ: promoting scientific and technological literac: in a critical perspective and fostering the political insertion of citizens in decision-ma+ing [3]. Besides formal education, scientific popularization activities ma: ta+e place in non-formal education conte9ts 8ith children and :oung people [4]. ntegrated in igher rofessional ducation stud: c:cle 8e developed a course that intended to ena le students to: promote scientific literac: and a8areness of environmental issues in children and :oung people@ appl: different forms of science popularization depending on the conte9t of intervention@ plan, implement and evaluate scientific popularization activities for children and :oung people. he research carried out included 20 students and used diverse instruments to collect data (2uestionnaires and studentsC productions). indings revealed that students ac2uired more mature ideas a out the purposes and the relevance of popularization of science, and an increasing recognition that and as future professionals 8ho 8ill intervene 8ith children and :oung people, the: ma: have an important role in the process.